İşçinin yönetime katılması - Adakale, Fatma Elif (Fen Bilimleri Enstitüsü, 1990)
Bu tez, İşçinin Yönetime Katılması kavramını tanım, amaçlar düşünceler ve uygulamalar bakımından çok boyutlu olarak inceleyerek şu anda Türkiye'deki durumu saptamayı ve öneriler getirmeyi amaçlamak tadır. İşçinin Yönetime Katılması ya da kısaca Yönetime Katılma kavram olarak üzerinde ortak görüşe varılamamış bir konudur. Bu yüzden ikinci bölümde konu ile ilgili farklı tanımlamalar, işçi, işyeri, işletme gibi kavramlar üzerinde durulmuş ayrıca Yönetime Katılma kavramına yakın kimi zaman onunla aynı anlamda kullanılan Endüstriyel Demokrasi, Birlikte Yönetim, Özyönetim. Kara Katılma kavramları karşılaştırılmıştır. Yönetime Katılma'nın tarihsel gelişimi, amaçları, yöntemleri ve düzeyi, konuları ve bu konuda ileri sürülen olumlu ve olumsuz düşüncelere yer verilmiştir. Üçüncü bölümde Yönetime Katılma konusunda dünyadaki uygulamalar gözden geçirilmiştir. Uygulama bakımından en karakteristik özellik gösteren sistemler ve uygulandıkları ülkeler ele alınmıştır. Fransa'da uygulanan İşçi Temsilcileri ve İşletme Komiteleri aracılığıyla Yönetime Katılma, Federal Almanya'da Birlikte Yönetim, İngiltere'de Ortak Danışma Sistemleri, Amerika Birleşik Devletleri 'nde Toplu İş Sözleşmeleri Yoluyla Yönetime katılma ve Yugoslavya'da Öz Yönetim incelenmiş ve Avrupa Ekonomik Topluluğu 'nda konuya yaklaşım özetlenmiştir. Dördüncü bölümde ise Yönetime Katılma Türkiye açısından ele alınmış, konunun tarihsel gelişimi ve bu süreç boyunca işçi ve işveren kuruluşlarının ileri sürdüğü fikirlere yer verilmiştir. Yönetime Katılma konusunda gerek İş Kanunları 'nda gerekse Sendikalar Kanunu'nda yer alan düzenlemelere yer verilmiştir. Ayrıca 1989 - 1990 dönemine ait metal ve petrol iş kollarından alman on tane toplu iş sözleşmesi incelenerek konunun şu anki uygulamaları açıklanmaya çalışılmıştır.

The purpose of this thesis, "Workers' Participation in Management" is to give related definitions, the objectives and to discuss the different views, and the present implementation methods. Thus; the existing sitution and implementation in Turkey is studied and suggestions are made within the scope of this thesis, This thesis comprises of four sections Part 1. Introduction Part 2. General concepts related to workers' participation in management Part 3. Implementation of workers' participation in management in the world. Part 4. Implementation of workers' participation in Management in Turkey Part 1. Introduction The worker and labour concepts in the modern sense of the world can be said to have come into existance after the industrial revaluation in the world. It is only after this revaluation that the need to study on the concept of industrial democracy and Workers' participation in mangement has occuried. So by the middle of the nineteenth century, the democracy movements in the world have directly effected the workers and the way how citizens protect their rights either by their representatives or directly themselves, the justification of workers' participation in management and decision making has been introduced and thus the idea of workers' participation in management has developed. In the earlier days of these organizational efforts, the workers have confined themselves to secure wage increases and better working conditions, while in later periods the demand to participation in management has begun. Due to these industrial and political democracy movements, workers at many industrial entreprises assumed control over production which meant a huge profit loose for the employers and the private owners. So it can be said that the formula of workers' participation in management has been developed as a solution against the workers' overall control of the production by the employers and unions. IX Part 2. General Concepts related to workers' participation in management A specific and clear-cut definition for the concept of workers' participation in management can not be given due to the changes observed in application in different countries. Nevertheless it can be summarized as the workers' right to protect their profit within the entreprise and establishment by having a part in the management. This right has a wide range, starting from very limited participation in management to self -management system. The objectives implementing workers' participation in management can be summarized as 1. Moral benefits 2. Social and political objectives 3. Economical objectives The methods of workers' participation in management can be grouped as 1. Advisor method 2. Consultant method 3. Management method Participation in management subjects can be subtitled as follows : Social field Personnel field Financial field Economic field But the extent of these fields may show differences from country to country. The industrial democracy concept may be regarded principally from five viewpoints: a) Productivity, b) Authority, c) Humanity, d) Security, and e) Private enterprise. It should be added further that the concept may show variations for each system, society and even individual. Several opinions were advenced, both for and against, the workers' participation in the management of the enterprise. According to those in favor of such participation, a) The participation in the management is not a prerogative arising from the investment of capital, b) It paves the way toward the social welfare, c) It cannot be considered as a corollary of the property rights, d) The labour of today is knowledgeable and experienced enough to participate in the management, e) It offers an idean solution for the industrial peace. On the other hand, those who reject the idea maintain that, a) The participation is a right arising from the capital ownership, b) It might prejudice the property rights, c) The proprietor runs a certain degree of risks which may be aggravated by the participation to management of people who do not risk their own capital, d) The labor is not sufficiently educated and trained to have a word in the management. Part 3. Implementation of Workers' Participation in Management Different systems are catagorized according to the main properties observed in the systems and these systems are mentioned by the name of the country that applies it widely. In France, the workers' participation in management is established by committee of entreprise and deletes of personnel. The reveant legal text have been modified in 1966 according to which the workers* participation in management of all entreprise employing more than 50 persons. In Germany, "Workes Constitution Act" allows the workers' participation in management in the bases: of establishment. Whereas Co-determination Act allows effectiveness to workers ' participation in management. This law is applied in Germany in region of mining industry and legal attempts are made being to have xt expanded to the rest of Germany. XI According to this system, waters' take part in supervisory and managing boards of the entreprise. The supervisory board is comprised of eleven members. Five of these members constitute the workers. Another five are the representatives of employers. The eleventh member is neutal member. Tne functions and competence of the supervisory board are very extensive and important. Managing board is comprised of all directors. One of the managers is the workers' manager. The functions of this board is also very extensive and important in the entreprise. This is the most effective system which allows maximum participation to workers administration mechanism of management. In United Kingdom, Joint Consultation Committee system in use. It only allows consultation between the committees and the management. So it is not considered very effective. In United States of America, Workers' Participation in management is not well-developed and the application area is limited by the collective bargaining agreements. Partly due to the fact that the labour unions are relunctant to commxt themselves. In Yugoslavia, the workers have complite control over production and management. The workers council - workers control bodies take over the management. In European Economic Community, the subject is still in discussion, due to the differnt systems adoped in European Economic Community member countries. The general expectation is the adoption of a system that will embrace the majority. Party 4. Implementation of Workers' Participation In Turkey With The Act No:440 which had entered into vigor in 1964 and introduced the system of representing the worker in the managing boards of some state economic entreprises by one worker representative, has been counted invalid after 1980 's. After this, until the present day, mentioning an effective workers' participation in management is not very possible. But the committees in work laws and collective bargaining agreements, may be mentioned as a way of application of workers' participation in management in Turkey. Conclusion: Workers' participation in management can be said to be provision of being a 20 th century developping cantry, Turkey, as the ootntry as the xxi way of European Economic Community membership should be well prepared for a probable effective system which shall be adopted by European Economic Community in near future. For this laws should fastly be formed. The system adopted in The West Germany may be taken as a sample method.
Workers participation in management
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1990
Keywords: Çalışma Ekonomisi ve Endüstri İlişkileri; Dünya; Türkiye; Yönetime katılma; İşçiler; Labour Economics and Industrial Relations; World; Turkey; Participation management; Workers